2012
DOI: 10.1016/j.contraception.2011.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Prostate-specific antigen as a biomarker of condom failure: comparison of three laboratory assays and self-reported condom use problems in a randomized trial of female condom performance

Abstract: Background-Prostate-specific antigen (PSA), a biomarker for semen exposure, may provide a more objective measure of condom failure than subject self-reports. Methods for measuring PSA vary and their comparability with respect to assessing condom performance has not been adequately evaluated. This study compared results from three different PSA assays of vaginal samples collected by subjects in a randomized clinical trial which compared the performance of female condoms.Study Design-We selected 30 pairs of pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
(47 reference statements)
1
10
0
Order By: Relevance
“…Real-time polymerase chain reaction (PCR) was used for detection of Y chromosome DNA as previously described [21]. The Y chromosome assay offers a qualitative indication of the presence of Y chromosome DNA (positive at >0 ng/mL); the assay also yields quantitative results that have been shown to decrease with time since exposure (detectable up to 14 days) [57].…”
Section: Methodsmentioning
confidence: 99%
“…Real-time polymerase chain reaction (PCR) was used for detection of Y chromosome DNA as previously described [21]. The Y chromosome assay offers a qualitative indication of the presence of Y chromosome DNA (positive at >0 ng/mL); the assay also yields quantitative results that have been shown to decrease with time since exposure (detectable up to 14 days) [57].…”
Section: Methodsmentioning
confidence: 99%
“…In many reproductive health studies, the use of semen biomarkers is often in addition to self-reported sexual behavior. Laboratory-confirmed presence of semen biomarkers in vaginal secretions is considered objective 22,24-27 as opposed to self-report, which is subject to several types of bias. When the research involves sensitive behaviors such as sex and condom use, reporting bias is known or suspected to occur.…”
Section: General Considerations For Determining the Need For Semen Bimentioning
confidence: 99%
“…27 In addition to reporting bias, sometimes participants are unaware of their exposure. 15,22 Participants in clinical trials evaluating barrier methods of contraception, for example, may not be aware of some exposures such as a condom slippage or breakage that results in small exposures to semen. 22,27 By contrast, some participants may report that they had an exposure or experienced issues with the condom, when the use of biomarkers yields negative results for semen exposure.…”
Section: General Considerations For Determining the Need For Semen Bimentioning
confidence: 99%
“…Biomarkers of semen exposure have been used in condom effectiveness [15], female condom [6], and microbicide trials [7], as well as other women's health research [813]. Most studies have used prostate-specific antigen (PSA), a robust biomarker for determining the presence of semen in vaginal fluid.…”
Section: Introductionmentioning
confidence: 99%